I have some questions for you - Makkai, Rebecca (2023)
"In the riveting new novel from the author of the Pulitzer Prize and National Book Award finalist The Great Believers, a woman must reckon with her past when new details surface about a tragedy at her elite New England boarding school"--
Keywords: Novels